Analyzing Writing Style and Adapting to a New Writing Culture: A Teaching Practice - Givens, Charity (Journal of Academic Writing, 2020)
This teaching practice presents a classroom exercise completed in a first-year composition class at an English-medium private university in Lithuania. The course typically takes place in the second semester of the year and is required for all first-year students, who are multilingual but completing their university degree in English. The instructor, a US speaker of English who has a background in US composition studies, leads the exercise that consists of a writing style analysis that examines sentence length, word variety, and sentence emphasis, concluding with a discussion of how students can adapt their writing style to meet the needs of a new audience. The exercise aims to help students understand their writing style and what they need to know to adapt their style to fit the academic writing context in the university.